2015
DOI: 10.1038/jhh.2015.77
|View full text |Cite
|
Sign up to set email alerts
|

Renal denervation for treatment of uncontrolled hypertension in an Asian population: results from the Global SYMPLICITY Registry in South Korea (GSR Korea)

Abstract: Reports detailing the response of hypertensive patients to renal denervation (RDN) in Asian patients are limited. We evaluated 6- and 12-month outcomes after RDN in an Asian population and compared outcomes to a primarily Caucasian population. The Global SYMPLICITY Registry (GSR) is a prospective, all-comer, worldwide registry that evaluates the safety and effectiveness of RDN and includes the Korean registry substudy (GSR Korea) and a Caucasian subset (GSR Caucasian). Given differences in baseline characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 25 publications
2
17
0
1
Order By: Relevance
“…These results are supported as well by multivariable analyses, in which higher baseline SBP was consistently associated with a greater reduction in both office and 24-h ambulatory SBP at all timepoints. Although this is the first multivariable analysis to our knowledge to examine predictors of BP change at 3 years, this finding is consistent with previous multivariable analyses of predictors of BP at 6 or 12 months after RDN 10 , 27 , 28 …”
Section: Discussionsupporting
confidence: 89%
“…These results are supported as well by multivariable analyses, in which higher baseline SBP was consistently associated with a greater reduction in both office and 24-h ambulatory SBP at all timepoints. Although this is the first multivariable analysis to our knowledge to examine predictors of BP change at 3 years, this finding is consistent with previous multivariable analyses of predictors of BP at 6 or 12 months after RDN 10 , 27 , 28 …”
Section: Discussionsupporting
confidence: 89%
“…Our observations are consistent with some of the other non-controlled studies that have been performed [6,8]. A recent analysis of the Global SYMPLICITY Registry in South Korea suggested that some Asian populations may have a greater response to RAD, compared to Caucasian patients [26]. The effect size we observed in BP reduction was similar to that observed in the Asian patients in their study.…”
Section: Discussionsupporting
confidence: 92%
“…Renal sympathetic activation leads to volume retention via increased sodium reabsorption, reduction of renal blood flow, and activation of the renin-angiotensin-aldosterone system via increased renin release from the juxta-glomerular apparatus, which are important for BP regulation293031. Theoretically speaking, sufficient disruption of sympathetic fibers via RDN is an effective non-pharmacological method to lower BP, which has been revealed by previous clinical researches781011. Meanwhile, our previous published basic study had shown that catheter-based RDN, no matter conducted by TC catheter or saline-irrigated catheter, could induce the significant damage to renal nerves28.…”
Section: Discussionmentioning
confidence: 96%
“…A series of clinical studies7891011 indicated that RDN could lead to significant blood pressure (BP) reduction in patients with resistant hypertension until to the Simplicity HTN-312 failed to demonstrate the superiority of RDN over pharmacological management of hypertension no matter for office BP or 24-hour ambulatory BP measurements. However, further evaluation of the Simplicity HTN-3 trial identified several potential confounding factors that may contribute to the negative results, including over-proportion of Afro-American participants, short of operative experience for RDN, insufficient 4-quadrant ablations, and antihypertensive medication changes1314.…”
mentioning
confidence: 99%